The Ravenglass eye - Fletcher, Tom (London : Jo Fletcher Books, 2012)
"Edie is a barmaid at the Tup in the small town of Ravenglass. So far, so normal. But when she is caught in a freak earthquake she subsequently develops 'The Eye' - a power that allows her glimpses of other worlds and strange events. At first Edie passes her visions off as nightmares, but when a corpse is found, murdered, she realises that she has seen this death before, and that her visions are not imaginery, but real. Mankind had better hope that Edie finds a solution to the murders soon, because it's more than just the influence of 'The Eye' that has entered the world. A power far more malevolent has been released, and that power is hungry for death." --Back cover.
Keywords: Paranormal fiction; Novels